Generational change in fasting glucose and insulin among children at ages 5-16y: Modelled on the EarlyBird study (2015) and UK growth standards (1990) (EarlyBird 69). (January 2017) - Mostazir, Mohammod; Jeffery, Alison; Voss, Linda; Wilkin, Terence
Highlights: We modelled the change in beta cell demand from the UK BMI standards of 1990 and the EarlyBird data set of 2015. HbA1C and fasting glucose showed no change, whereas fasting insulin and HOMA2-IR suggested a substantial rise in beta cell demand, particularly in girls. Beta cell demand is an important cause of beta cell loss, and the observations provide a possible basis for the rise in dysglycaemia and type 2 diabetes among contemporary children. Abstract: Aim: Pre-diabetes is a state of beta-cell stress caused by excess demand for insulin. Body mass is an important determinant of insulin demand, and BMI has risen substantially over recent time. We sought to model changes in the parameters of glucose control against rising BMI over the past 25 years. Methods: Using random coefficient mixed models, we established the correlations between HbA1C, fasting glucose, fasting insulin, HOMA2-IR and BMI in contemporary (2015) children ( N = 307) at ages 5-16y from the EarlyBird study, and modelled their corresponding values 25 years ago according to the distribution of BMI in the UK Growth Standards (1990). Results: There was little change in HbA1C or fasting glucose over the 25y period at any age or in either gender. On the other hand, the estimates for fasting insulin and HOMA2-IR were substantially higher in both genders in 2015 compared with 1990. Conclusion: Insofar as it is determined by body mass, there has been a substantial rise in beta cell demand among children over the past 25 years. The change could be detected by fasting insulin and HOMA2-IR, but not by fasting glucose or HbA1C.